Clinical validity of consultant technical skills assessment in the English National Training Programme for Laparoscopic Colorectal Surgery. Issue 8 (21st May 2015) - Mackenzie, H; Ni, M; Miskovic, D; Motson, R W; Gudgeon, M; Khan, Z; Longman, R; Coleman, M G; Hanna, G B
Abstract: Background: The English National Training Programme for Laparoscopic Colorectal Surgery introduced a validated objective competency assessment tool to accredit surgeons before independent practice. The aim of this study was to determine whether this technical skills assessment predicted clinical outcomes. Methods: Established consultants, training in laparoscopic colorectal surgery, were asked to submit two operative videos for evaluation by two blinded assessors using the competency assessment tool. A mark of 2·7 or above was considered a pass. Clinical and oncological outcomes were compared above and below this mark, including regression analysis. Results: Eighty-five consultant surgeons submitted 171 videos. Of these, 44 (25·7 per cent) were in the fail group (score less than 2·7). This low scoring group had more postoperative morbidity (25 versus 8·7 per cent; P = 0·005), including surgical complications (18 versus 6·3 per cent; P = 0·020) and fewer lymph nodes harvested (median 13 versus 18; P = 0·004). A score of less than 2·7 was an independent predictor of surgical complication, lymph node yield and distal resection margin clearance. Consultants with higher scores had performed similar numbers of laparoscopic colorectal operations (median 37 versus 40; P = 0·373) but more structured training operations (18 versus 9; P < 0·001). Conclusion: An objective technical skills assessment provided a discriminatory tool with which to accredit laparoscopic colorectal surgeons. Abstract : Discriminates competency